GE_GERICHTE P/14471/2023 vom 25. Juni 2025 - GE Cour de justice (2025)
VOL(DROIT PÉNAL);PRÉSOMPTION D'INNOCENCE;LIBRE APPRÉCIATION DES PREUVES;FRAIS JUDICIAIRES | CP.139.al1.leta; CPP.10; CPP.428; CPP.429.al1.leta